Cameroon coffee producers unite to sell - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Cameroon's much appreciated robusta coffee is not doing well. Quality has dropped because of problems in organising production and marketing. Fifteen rural organisations in the Mungo basin area have taken the situation to hand and are pooling their...